Quality Analysis Of Seameo Recfon Website Using The Webqual Method - Dodi Suswandi (Journal of Social Research, 2024)
his study aims to analyze and measure the quality of the SEAMEO RECFON website. The method used in this research is the Webqual method, which is a method or technique for measuring website quality based on end user perceptions which is used as the main reference with indicators of usability, information quality, and service interaction and the Importance Performance Analysis method. Data collection was carried out using a questionnaire of 50 questionnaires. The results showed that the level of user satisfaction with functionality has been achieved, while the level of user satisfaction with information quality has not been achieved, and the quality-of-service interaction has not been achieved. Based on the assessment of the three measurement dimensions, the usability dimension has a value of (0.245), the service interaction dimension has a difference or gap value of - (0.39) and the information dimension has a difference or gap value of - (0.26). Based on this, it can be concluded that the actual perception of quality has not been able to meet the ideal quality desired by SEAMEO RECFON website users, especially from quality attributes related to information on the website.